The role of psychiatrists in diagnosing conversion disorder: a mixed-methods analysis - Kanaan, Richard A (Neuropsychiatr Dis Treat, 2016)
OBJECTIVE: Since DSM-5 removed the requirement for a psychosocial formulation, neurologists have been able to make the diagnosis of conversion disorder without psychiatric input. We sought to examine whether neurologists and specialist psychiatrists concurred with this approach. DESIGN: We used mixed methods, first surveying all the neurologists in the UK and then interviewing the neuropsychiatrists in a large UK region on the role of psychiatrists in diagnosing conversion disorder. RESULTS: Of the surveyed neurologists, 76% did not think that psychiatrists were essential for the diagnosis and 71% thought that psychiatrists did not even consider conversion disorder when referred a case. The neuropsychiatrists who were interviewed held complex models of conversion disorder. They believed all cases could be explained psychosocially in theory, but the nature of the diagnostic encounter often prevented it in practice; all felt that psychosocial formulation could be very helpful and some felt that it was essential to diagnosis. CONCLUSION: Although neurologists do not think psychiatrists are required for diagnosing conversion disorder, specialist psychiatrists disagree, at least in some cases.